Indonesian E-Commerce (IOT) Service Quality as Impacting Customer Satisfaction - daniel rompas; ra fera ratna wijayanti (LIAISON JOURNAL OF BEST, 2023)
Nowadays, technology has made the way of running business become different than before. With the presence of technology, a lot of businesses utilize and take advantage from it in order to make the run of business be easier, simpler, and smoother than the conventional way. The Internet of Thing (IoT) from technology enables businesses to sell products and services through online platform such as E-Commerce marketplace, online delivery of food and beverage, and also online taxi & motorcycle. Businesses and online sellers can put their goods in the internet and will get wider range of customers and audience. Many of business players even closed their physical store and only have a warehouse to store the goods in order to decrease the expenses budget. Customers can buy needs and wants from anywhere and anytime only by order and do the payment, the package will be delivered to their chosen location. The crucial things that an online businesses must have is a Service Quality and Marketing Mix 4P’s (Product, Price, Promotion, Place). By well performance of Service Quality and Marketing Mix 4P’s, it will lead to Customers Satisfaction where the customers are happy and satisfied by doing the interaction with the online business. This research study used quantitative research to analyze the influence of Service Quality and Marketing Mix 4P’s on Customers Satisfaction in Indonesian e-commerce marketplace. The main topic of this research study is Indonesian online businesses, all type of online businesses are included such as online delivery of food and beverage sector, online taxi car & taxi motorcycle, especially e-commerce marketplace. The author has distributed 272 Keywords: E-Commerce,Marketing Mix, Service Quality, Customer Satisfaction.